Effect of E-Commerce, Use of Accounting Information Systems and Business Capital in Student Decision Making for Entrepreneurship: Pengaruh E-Commerce, Penggunaan Sistem Informasi Akuntansi dan Modal Usaha Dalam Pengambilan Keputusan Mahasiswa Untuk Berwirausaha - Choirina Nurlaila; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of (1) E-commerce, (2) the use of Accounting Information Systems and (3) Business Capital on student decision making for entrepreneurship. The research method uses quantitative. The study used primary data with a questionnaire. Students of the accounting study program at Muhammadiyah Sidoarjo University with as many as 88 respondents were the population in this study. Purposive sampling technique used in determining the sample. SPSS version 23.0 software assistance in data processing. In analyzing the data using multiple linear regression method. The results of the study prove that (1) E-commerce and (2) the use of accounting information systems have an influence on students' decision making for entrepreneurship, while (3) venture capital has no influence on entrepreneurial decisions.